Pemodelan Sebaran dan Waktu Tinggal Limbah Panas di Teluk Bontang - Suprijo, Totok; Romawan, Francis Seravino; Nur, Ashadi Arifin; Mandang, Idris; Napitupulu, Gandhi (Institut Teknologi Bandung, 2024)
Abstract The water mass exchange process between a bay and an open sea can flush effluents or pollutants that enter the bay. This paper describes a two-dimensional numerical modelling study on thermal water dispersion due to hydrodynamic processes in The Bontang Bay and the bay flushing capability. The numerical model used is Delft3D. Model input data was including bathymetry, water elevation, discharge of seawater intake and outfall, wind speed, and temperature of the thermal water effluent discharged into Bontang Bay. The modelling results were verified with observation data. Verification results shows that error of water elevation is 0.07 m, while current speed error is 0.26 m/s. Dispersion modeling results indicate that 40°C thermal water discharged at a rate of 24.6 m³/s into Bontang Bay has increased the water temperature in the bay by 1°C to 2°C. This increase in temperature potentially has a negative impact on aquatic ecosystems. An increase in water temperature of 1°C and 2°C covers areas of 19.32 km² and 7.26 km² in the bay, respectively. The residence time of thermal water in Bontang Bay is 3 days and 12 hours before flushing. Keywords: Thermal dispersion, exchange process, residence time, flushing time